Is CSR a motivator for socially responsible customers of for-profit social enterprises? - Mendoza, Enrico Cinco (Jurnal Studi Komunikasi, 2020)
The rise and development of corporate social responsibility (CSR) as a very significant and influential dogma in current business practice supports the popularly held view that firms cumulatively enjoy substantial power and control over a vast majority of society’s resources. Such enormous power can be at times detrimental to society in general and as such it is just right that these corporate behemoths police themselves unilaterally and be of good service to the community. The objective of this research is to evaluate the bivalent effects as motivator and hygiene factor of CSR on socially responsible customers towards a for-profit social enterprise. This research also evaluates the significance of CSR towards customer relationship and positive word of mouth among Human Nature customers. Respondents in this study were the customers of an independent distributor of Human Nature products in the Philippines. Findings indicated that CSR wields a significant influence towards customer in enhancing customer relationship and CSR helps in encouraging customers to willingly support and endorse Human Nature products. CSR also exhibits bivalently both characteristics of motivator and hygiene factor in moderating the impact of perceived CSR towards relationship quality and positive word of mouth from customers. Results of this study can be used as a reinforcement to the idea that CSR can and could elicit positive attitude and behavior from customers. Furthermore, results of this study can also be used by scholars in further probing the corporate impact of various individual CSR initiatives instead of CSR itself in its totality.